Faktor-faktor yang mempengaruhi peningkatan disiplin kerja pegawai :: Sekretariat Wilayah Daerah Tingkat II Kotamadya Cirebon; Studi kasus peningkatan disiplin aparat pegawai di Sekretariat Wilayah Daerah Tingkat II Kotamadya Cirebon Prop. Jawa Barat - ATO`ULLAH, ATO`ULLAH (Universitas Gadjah Mada, 1998)
The reseach which the title of "The factors which influenced on increasing of personnel's discipline on work ( A case study of increasing of personnel's discipline on bon Municipality, Province of West Java) mean6 to know nel's discipline on work. To know the increasing of personnel's discipline on work, the author use the three variabless, namely, motivation. leadership and peception of work. Based on the research indicated that the dominant f o c t o r which influenced on increasing of personnel's discipline on work is a leadership variable with the indicators that has a high score, namely; value of leadership model, characteristic of leadership, delegation of 1.ower's credibility and the m odal of leadership approach - - namely; participative and col-legialto the lower. While the second valued alternative which can be influenced on inceasing the discipline is a motivation variable with its indicators, namely; the wish of occuping on the higher position, the deEjire of better life-will and the need of social status. Then, the third alternative is the low of perception value which indicated by some indicators -there are an understanding o f j o b that imlpemented by personnel and the mastery of j o b that given by a leader. In o rder to increase the personnel's motivation in implementing a work discipline must be created a situation of harmonic and g ood work enviroment. To grow an internal motivation, especially in welfake of personnel, the Administative Secretariat of Cirebon Municipality should found a personnel cooperative to fulfill a primer material and to save and to b orow some money. Then the personnel8 of Ahinistative Secretariat of Cirebon Municipality should be given as whole p o s s i b l e to participate in making an important decision of organisation.